Interior Design of Organic Restaurant From Farm To Table in Pandaan - Ambar Mulyono; Citra, Aurellia (Faculty Of Arts and Design Sebelas Maret University, 2024)
The development and competition of the food industry are currently skyrocketing in tandem with the progress of the times and the growth of the world population. To swiftly expand the food supply, a variety of physical and chemical techniques are created and put to use. Indirectly or directly, this lowers the value of healthy food, which has detrimental effects including the widespread availability of processed fast food, which encourages unhealthy eating habits and lifestyles. One of the reasons consumers choose fast food is lifestyle change, which makes quick food that has a savory flavor and small servings a suitable choice. Unfortunately, ready-to-eat food does not provide enough nutrition and nutrients needed. Thus, a common attempt to ensure that the body gets all the nutrients it requires is to lead a healthy lifestyle and consume organic food. Pandaan's organic restaurants' design still falls short of raising people's understanding of the value of eating healthfully. Given this, the field of interior design must play a part in interior design, which includes educating the public about the significance of maintaining consumption that enters the body through restaurant design. This restaurant design plan aims to sell food and beverages, provide comfort, arrange, shop, receive, and process commodities, and entice customers to visit. It is believed that this farm-to-table organic restaurant's design would address the issues faced by the restaurant. Keywords: Interior, Restaurant, Food, Farm to Table